2009
DOI: 10.3892/ijo_00000316
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant epigenetic modifications in the CTCF binding domain of the IGF2/H19 gene in prostate cancer compared with benign prostate hyperplasia

Abstract: Abstract. Expression of the imprinted genes insulin-like growth factor 2 (IGF2) and H19 depends on the methylation pattern of their common imprinting control region (ICR) located on chromosome 11p15. As the somatic imprinting pattern may be lost during tumorigenesis due to epigenetic alterations, in the present study, we analyzed the DNA methylation and histone modifications in the differentially methylated region (DMR) of IGF2/H19 in benign prostate hyperplasia (BPH) and prostate carcinoma (PCa). Sodium bisul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…This local hypomethylation suggests a tight regulatory mechanism that is most likely mediated by locusspecific recruitment of DNA-modifying or binding factors that protect DNA from methylation by DNA methyltransferases. Such tumor-specific regulation of CTCF-binding sites by methylation is known (27). It has even been shown that CTCF itself can regulate DNA methylation patterns and that cancerous or immortalized cells, when compared with normal cells, have a distinct CTCFbinding landscape in the genome (28), highlighting the complexity of methylation-related regulation, especially when addressed in a locus-specific manner.…”
Section: Pace4 Splicing Is Regulated By Intraexonic Dna Methylationmentioning
confidence: 99%
“…This local hypomethylation suggests a tight regulatory mechanism that is most likely mediated by locusspecific recruitment of DNA-modifying or binding factors that protect DNA from methylation by DNA methyltransferases. Such tumor-specific regulation of CTCF-binding sites by methylation is known (27). It has even been shown that CTCF itself can regulate DNA methylation patterns and that cancerous or immortalized cells, when compared with normal cells, have a distinct CTCFbinding landscape in the genome (28), highlighting the complexity of methylation-related regulation, especially when addressed in a locus-specific manner.…”
Section: Pace4 Splicing Is Regulated By Intraexonic Dna Methylationmentioning
confidence: 99%
“…IGF2 expression is elevated in ovarian, colorectal and breast cancer associated with poor prognosis (Cardillo et al 2003, Sayer et al 2005, Kalla Singh et al 2007, Pollak 2008a, Huang et al 2010 and increased cell motility (Diaz et al 2007). Dysregulated expression of IGF2 in PC tumours and in surrounding prostate and stromal tissue occurs partially through loss of imprinting (Van Roozendaal et al 1998, Cui et al 2003, Poirier et al 2003, Bhusari et al 2011, Wang et al 2011 and correlates with tumour vs benign hyperplasia (Paradowska et al 2009); however, tumour IGF2 expression levels are not reflected in serum (Rowlands et al 2009(Rowlands et al , 2012. IGF2 can signal through the IGF1 receptor (IGF1R) or via the insulin receptor (INSR) to elicit insulin-like signalling (Cardillo et al 2003, Pandini et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…2A), immediately upstream of the miR-483 stem loop, has strong insulator activity and binds to the CTCF repressor (22). CTCF is an important methyl-sensitive regulator of transcription involved in the epigenetic regulation of genomic imprinted loci such as the IGF2/H19 locus in 11p15.5, and is involved in Wilms' tumor (23,24), breast cancer (25,26), and prostate cancer (27). We decided to determine whether CTCF is also involved in the repression of the IGF2/mir-483 genomic regions we cloned.…”
Section: Zinc Finger Ccctc-binding Factor Ctcf Represses the Genomic mentioning
confidence: 99%